2005
DOI: 10.1007/s11270-005-8202-y
|View full text |Cite
|
Sign up to set email alerts
|

Resource manipulation in uranium and arsenic attenuation by Lemna gibba L. (duckweed) in tailing water of a former uranium mine

Abstract: Influences of phosphorus and nitrogen on uranium and arsenic accumulation in Lemna gibba L. were investigated in the laboratory hydroponic cultures and in the field pot experiments. The initial uranium and arsenic concentrations in solutions for the hydroponic cultures were 1000 µg l −1 each, while in situ trials used tailing water containing 198.7 ± 20.0 µg U l −1 and 75.0 ± 0.4 µg As l −1 at a former uranium mine in eastern Germany. A test of three PO 3− 4 concentrations (0.01, 13.6 and 40.0 mg l −1 ) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 47 publications
0
14
0
1
Order By: Relevance
“…A similar phenomenon was reported by Huang et al (2004) in As-hyperaccumulating ferns. Mkandawire et al (2005) observed that As accumulation in duckweed increased slightly with an increase in NH 4 + concentration. The increase in As accumulation in plants supplied with NH 4 -N fertilizer is probably due to the enhancement of uptake and/or accumulation of AsO 4 3− by an ion synergistic effect of NH 4 + .…”
Section: Discussionmentioning
confidence: 90%
“…A similar phenomenon was reported by Huang et al (2004) in As-hyperaccumulating ferns. Mkandawire et al (2005) observed that As accumulation in duckweed increased slightly with an increase in NH 4 + concentration. The increase in As accumulation in plants supplied with NH 4 -N fertilizer is probably due to the enhancement of uptake and/or accumulation of AsO 4 3− by an ion synergistic effect of NH 4 + .…”
Section: Discussionmentioning
confidence: 90%
“…ex Hensch. (Overall and Parry, 2004), Lemna gibba L. (Mkandawire et al, 2004(Mkandawire et al, , 2005Sasmaza and Obek, 2009), Spirodela punctata (G.Mey.) C.-H.Thomps.…”
Section: Uranium Accumulation Trend In Plantsmentioning
confidence: 99%
“…The transfer of radionuclides from soils to plants is dependent on three classes of factors [129,214,314]:…”
Section: Phytoremediationmentioning
confidence: 99%
“…Considering the effects of various soil amendments on uranium desorption from soil to soil solution, a number of authors investigated the physiological characteristics of uranium uptake and accumulation in plants, and developed techniques to trigger uranium hyperaccumulation in plants [313,314]. Their studies indicate that soil organic matter sequestered uranium, rendering it largely unavailable for plant uptake [265].…”
Section: Phytoremediationmentioning
confidence: 99%